The Performances of Environmental Control Systems to Hydroponics Agriculture Based on Microcontroller - Sobari, Enceng; Vernanda, Dwi; Nugraha Purnawan, Nunu; Herdiawan Apandi, Tri; Aliyawan Aris, Muhammad (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
Hydroponic cultivation is one of the common modern farming systems. The effectiveness of the agricultural system refers to the appropriate environmental factors that can be controlled such as temperature, humidity, light intensity, and concentration of solutions that support the growth of cultivated plants. Hydroponic farming will develop increasingly as long as it is supported by technological aspects that are able to control the environmental factors automatically. The objective of this research is to come up with a device that can measure environmental factors as indicators of hydroponic farming using a microcontroller-based controller system. The method used is the measurement test method, which consists of testing the parameters of air temperature, humidity, water temperature, light intensity, nutrient concentration, and pump work, which are then reviewed by literature studies. The results showed that the air temperature sensor (DHT11) had an average temperature accuracy of 22.7-25.3 oC, the humidity sensor (RH) had an average accuracy of 50% - 73.6%. Light intensity sensor (BH1750) averaged to 1289 lx. While the solution of height sensor (HC-SR04) was able to read a 25% decrease in solution for 1 week. Moreover, nutrition concentration sensor testing (TDS Probe) provided an accuracy of the average nutritional concen-tration of 1493 ppm for 24 hours.